Pendidikan Berbasis Kearifan Lokal dalam Penguatan Profil Pelajar Pancasila - Aisyah, Siti; Shokib Rondli, Wawan (ILUMINASI: Journal of Research in Education, 2024)
The rapid development of technology can shift local wisdom in society if local-based learning is not implemented early on. This shift occurs because there is no clear boundary between local culture and outside culture. The curriculum in Indonesia has undergone several curriculum changes. However, learning activities are required to emphasise the local wisdom of students. This research uses the literature review method. The literature review method in this study is used to identify the presence or absence of research progress through the results of literature related to the topic of local wisdom- based education in the new paradigm of education which is part of the independent curriculum, especially in strengthening the profile of strengthening Pancasila in the 21st century. The strategy used by researchers in searching for articles is to search using keywords at the National Library of Indonesia. The purpose of this research is to analyse local-based education in strengthening the profile of Pancasila students in the 21st century. The results showed that local wisdom is indispensable in strengthening the profile of Pancasila students in the 21st century.